CrimsonHex: a learning objects repository for programming exercises1. (13th June 2012) - Queirós, Ricardo; Leal, José Paulo
SUMMARY: A repository of learning objects is a system that stores electronic resources in a technology‐mediated learning process. The need for this kind of repository is growing as more educators become eager to use digital educational contents and more of it becomes available. The sharing and use of these resources relies on the use of content and communication standards as a means to describe and exchange educational resources, commonly known as learning objects. This paper presents the design and implementation of a service‐oriented repository of learning objects called crimsonHex. This repository supports new definitions of learning objects for specialized domains and we illustrate this feature with the definition of programming exercises as learning objects and its validation by the repository. The repository is also fully compliant with existing communication standards and we propose extensions by adding new functions, formalizing message interchange and providing a REST interface. To validate the interoperability features of the repository, we developed a repository plug‐in for Moodle that is expected to be included in the next release of this popular learning management system. Copyright © 2012 John Wiley & Sons, Ltd.